Dissipation, quantum coherence, and asymmetry of finite-time cross-correlations - Tan Van Vu; Van Tuan Vo; Keiji Saito (Physical Review Research, 2024)
Recent studies have revealed a deep connection between the asymmetry of cross-correlations and thermodynamic quantities in the short-time limit. In this study, we address the finite-time domain of the asymmetry for both open classical and quantum systems. Focusing on Markovian dynamics, we show that the asymmetry observed in finite-time cross-correlations is upper bounded by dissipation. We prove that, for classical systems in a steady state with arbitrary operational durations, the asymmetry exhibits, at most, linear growth over time, with the growth speed determined by the rates of entropy production and dynamical activity. In the long-time regime, the asymmetry exhibits exponential decay, with the decay rate determined by the spectral gap of the transition matrix. Remarkably, for quantum cases, quantum coherence is equally important as dissipation in constraining the asymmetry of correlations. We demonstrate an example where only quantum coherence bounds the asymmetry while the entropy production rate vanishes. Furthermore, we generalize the short-time bounds on correlation asymmetry, as reported by Shiraishi [Phys. Rev. E 108, L042103 (2023)2470-004510.1103/PhysRevE.108.L042103] and Ohga et al. [Phys. Rev. Lett. 131, 077101 (2023)0031-900710.1103/PhysRevLett.131.077101], to encompass finite-time scenarios. These findings offer insights into the thermodynamic aspects of correlation asymmetry.